Structural Analysis of Steel Transmission Towers for Large River Crossing of Overhead Transmission Lines: A Case Study in Brazil - Rechtman, M. S.; Motta, J. N. M.; Menezes, A.; da Silva, J. G. S.; Longo, O. (Engineering, Technology & Applied Science Research, 2020)
This study aims to investigate the structural behavior of steel transmission towers used for large river crossings. Design standards usually applied to analyze these structures don’t consider situations in which the transmission towers are used in river crossings. In Brazil, due to the fact that it is necessary to cross large areas owing to the rivers’ size, these towers assume great heights. It should be noted that the towers can weigh up to 24,500kN and exceed 300m in height. The current study develops an analysis that surpasses the existing standard methodologies, aiming for a structural optimization compatible with vast crossings and new materials, aiming to resolve this design challenge regarding power transmission lines. To do this, a river crossing spanning 2,300m, situated in the northern region of Brazil, was studied based on the use of three different conductor configurations, electrically equivalent, commonly used wind design standards, and structural solutions utilizing tubular and angle profiles.